DAMPAK PRODUK DOMESTIK REGIONAL BRUTO (PDRB) TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN MAMASA - BUNYAMIN BUNYAMIN (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
This study aims to determine the impact of Gross Regional Domestic Product (GDP) of the Revenue Mamasa, and to find out how big the impact of Economic Growth of Revenue. To analyze the economic growth and revenue using time series analysis. Based on the research results it can be concluded as follows: Revenue Indicator Gross Regional Domestic Product (GDP), very influential on the Revenue. The amount of revenue impact on economic growth with GDP indicator of 93.71%. The calculation of GDP is used in the District of GDP based Mamasa current price.